Effects of Proteases from Pineapple and Papaya on Protein Digestive Capacity and Gut Microbiota in Healthy C57BL/6 Mice and Dose-Manner Response on Mucosal Permeability in Human Reconstructed Intestinal 3D Tissue Model - Olha Kostiuchenko; Nadiia Kravchenko; Jan Markus; Stephen Burleigh; Olexandr Fedkiv; Ling Cao; Silvia Letasiova; Galyna Skibo; Frida Fåk Hållenius; Olena Prykhodko (Metabolites, 2022)
Cysteine proteases obtained from the stem of pineapple or papaya latex, bromelain and papain, respectively, exhibit a broad spectrum of beneficial effects on human health. However, their effects on gut microbiota composition or dose-manner effects on the intestinal integrity of healthy tissue have not been evaluated. In this study, C57BL/6 young, healthy mice were fed bromelain or papain in a dose of 1 mg per animal/day for three consecutive days, followed by the assessment of digestive protein capacity, intestinal morphology and gut microbiota composition. Furthermore, a human reconstructed 3D tissue model EpiIntestinal (SMI-100) was used to study the effects of 1, 0.1 and 10 mg/mL doses of each enzyme on tissue integrity and mucosal permeability using TEER measurements and passage of Lucifer Yellow marker from the apical to the basolateral side of the mucosa. The results indicated that fruit proteases have the potential to modulate gut microbiota with decreasing abundance of Proteobacteria and increasing beneficial Akkermansia muciniphila. The enhancement of pancreatic trypsin was observed in bromelain and papain supplementation, while bromelain also increased the thickness of the ileal mucosa. Furthermore, an in vitro study showed a dose-dependent interruption in epithelial integrity, which resulted in increased paracellular permeability by the highest doses of enzymes. These findings define bromelain and papain as promising enzymatic supplementation for controlled enhancement of paracellular uptake when needed, together with beneficial effects on the gut microbiota.